2009
DOI: 10.2967/jnumed.108.055665
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Perfusion in Nonischemic Dilated Cardiomyopathy With and Without Atrial Fibrillation

Abstract: Recent studies have shown that idiopathic atrial fibrillation (AF) is associated with diminished myocardial perfusion and perfusion reserve, which are also impaired in various forms of cardiomyopathies. In many cases, AF develops during progression of dilated cardiomyopathy (DCM) and may aggravate heart failure. This study compared myocardial perfusion between patients with nonischemic DCM with and without AF. Methods: Twelve men (age 6 SD, 55 6 12 y) who had DCM and persistent AF were compared with a group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 32 publications
3
9
0
1
Order By: Relevance
“…Other studies indicated that acute AF causes a decline in diastolic coronary flow and promotes sub-endocardial ischemia [31]. Similar changes have been shown among AF patients with hypertrophic cardiomyopathy [32], and dilated cardiomyopathy [33], proving that AF may be a causative factor and not merely a bystander. AF patients are more likely to have positive SPECT finding for ischemia, yet have a lower yield of significant CAD by SCAG (15% for AF patients vs. 67% in n-AF; p=0.006) [34].…”
Section: Af and Coronary Ischemiasupporting
confidence: 52%
“…Other studies indicated that acute AF causes a decline in diastolic coronary flow and promotes sub-endocardial ischemia [31]. Similar changes have been shown among AF patients with hypertrophic cardiomyopathy [32], and dilated cardiomyopathy [33], proving that AF may be a causative factor and not merely a bystander. AF patients are more likely to have positive SPECT finding for ischemia, yet have a lower yield of significant CAD by SCAG (15% for AF patients vs. 67% in n-AF; p=0.006) [34].…”
Section: Af and Coronary Ischemiasupporting
confidence: 52%
“…In this paper we describe a rest/stress [ 11 C]acetate PET imaging protocol that can effectively yield measurement of the myocardial blood flow [3,4,6,[24][25][26] [30]. Another approach was to use [ 13 N]ammonia with dipyridamole to investigate the effect of long-terms inhibition of the angiotensin converting enzyme or Beta blocker [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, myocardial ischaemia and/or impairment of myocardial microcirculation have been shown in patients with AF despite normal epicardial coronary arteries. Various methods have been used to measure coronary flow in AF patients, including intracoronary Doppler flow wire [3], position emission tomography (PET) [4][5][6] and single-photon emission computed tomography (SPECT) [1,[7][8][9], and it has been reported that impaired coronary blood flow is associated with unfavorable outcomes in patients with AF [7,8].…”
Section: Introductionmentioning
confidence: 99%